2020
DOI: 10.1016/j.enbuild.2020.109935
|View full text |Cite
|
Sign up to set email alerts
|

Future heating and cooling degree days for Belgium under a high-end climate change scenario

Abstract: The local outdoor climate and building characteristics influence the energy use of a building to an important extent. To design energy efficient and climate robust buildings, it is important to get insights into the energy demand over the building's service life from the early design phase onwards. This paper presents an overview of the different variants of the heating and cooling degree day method. A convection-permitting climate model is furthermore used to obtain heating and cooling degree days (for a base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Nonetheless, for the Sydney region, Argüeso et al (2015) showed that urbanization reinforces local warming, but conversely decreases the trend of increasing humidity. Ramon et al (2020) revealed a 27% decline in heating degree-days over Belgium due to more pronounced regional warming in urban areas only captured by a CPRCM. Using CPRCM outputs to force a building energy model for Tokyo, Arima et al (2016) showed a substantial increase in sensible and latent heat load in the next decade.…”
Section: Urban Climate and Land Use Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, for the Sydney region, Argüeso et al (2015) showed that urbanization reinforces local warming, but conversely decreases the trend of increasing humidity. Ramon et al (2020) revealed a 27% decline in heating degree-days over Belgium due to more pronounced regional warming in urban areas only captured by a CPRCM. Using CPRCM outputs to force a building energy model for Tokyo, Arima et al (2016) showed a substantial increase in sensible and latent heat load in the next decade.…”
Section: Urban Climate and Land Use Changesmentioning
confidence: 99%
“…Helsen et al (2020) found that two different CPRCMs show consistent scale-dependency of the future increase in daytime summer hourly extreme precipitation, with larger differences in the climate change signals over flatlands than over mountainous regions. Using a CPRCM, Ramon et al (2020) were able to identify local temperature differences at the regional level and obtained better precision for the degree-days computation using hourly values.…”
Section: Belgiummentioning
confidence: 99%
“…The changes in energy use highlight the need for adaptation and mitigation strategies. Since the existing climate zones may change in the future [48], as well as heating and cooling degree days [49,50], any new or updated regulation should consider these changes [51]. Moreover, inadequate sizing of systems could lead to energy inefficiency or discomfort.…”
Section: The Implications Of Changing Energy Needsmentioning
confidence: 99%
“…Spinoni et al (2018) [14] a lso applied HDD-CDD indicators to investigate whether energy demands for cooling and heating of buildings are projected to rise or fall due to climate change. Similarly, Andrade et a l. (2021) [15] Many researchers have reported the Mediterranean region as one of the most vulnerable areas to the projected climate change [14][15][16][17][18][19][20]. The current climate projections predict extreme weather events in the region in response to the warmer and drier periods in the near future.…”
Section: Introductionmentioning
confidence: 99%